Implementation of Archives Digitalization through Belajar.id Account in Improving Data Organization - Riwayati, Ririn (PPSDP International Journal of Education, 2024)
The purpose writing this article is to understand the process of structuring digitized data at SDN 8 Rambang, due to archive services conventional which is ineffective and we are trying to change to a digital archive service. Due to the preservation of archives in the current era of Society 5.0 leads to how the public can access archival information that is capable of implementing technology in it. Archive arrangement includes several types of archives including textual, audio and audio-visual archives. The process of moving current archive contents saving it in different media, takes place continuously from old media to new media. Both documents and archives that are in digital format or still analog. Document digitization/archives are a process of change from conventional ones in various styles and forms to electronic archives.